The Functional Role Of Fish Protein Hydrolysate Derived Bioactive Compounds In Cardioprotection And Antioxdative Functions - R.VIGNESH; M.SRINIVASAN; N. JAYAPRABHA; M.A.BADHUL HAQ (International Journal of Pharma and Bio Sciences, 2012)
Bioactive peptides isolated from various fish protein hydrolysates have shown a numerous bioactivities such as antihypertensive, antithrombotic, immunomodulatory and antioxidative activities. Fish protein hydrolysate extracts performs the regulation of the immune system, gastrointestinal functions, blood pressure, glucose inhibitory activity, antihypertensive effect, antioxidant properties and angiotensin converting enzyme inhibitory activity. Fish waste is rich in potentially valuable oils, minerals, enzymes, pigments and flavors etc. These may also have many alternative uses in food, pharmaceutical, agricultural, aquaculture and industrial applications. Fish proteins can have not only nutritional but also functional and biological applications. Intake of fish oil, which is an excellent source of omega- 3 fatty acids, has been linked to promotion of human health to fight against numerous diseases. Peptides derived from fish proteins have shown the ability of exerting potent antioxidative activities in different oxidative systems. This review paper focuses on the important role of fish protein extracts in various pharmacological aspects.